Marine Biotoxins: Occurrence, Toxicity, Regulatory Limits and Reference Methods - Visciano, Pierina; Schirone, Maria; Berti, Miriam; Milandri, Anna; Tofalo, Rosanna; Suzzi, Giovanna (Frontiers in Microbiology, 2016)
Harmful algal blooms are natural phenomena caused by the massive growth of phytoplankton that may contain highly toxic chemicals, the so-called marine biotoxins causing illness and even death to both aquatic organisms and humans. Their occurrence has been increased in frequency and severity, suggesting a worldwide public health risk. Marine biotoxins can accumulate in bivalve molluscs and regulatory limits have been set for some classes according to European Union (EU) legislation. These compounds can be distinguished in water- and fat-soluble molecules. The first group involves those of Paralytic Shellfish Poisoning and Amnesic Shellfish Poisoning, whereas the toxins soluble in fat can cause Diarrhoeic Shellfish Poisoning and Neurotoxic Shellfish Poisoning. Due to the lack of long-term toxicity studies, establishing tolerable daily intakes for any of these marine biotoxins was not possible, but an acute reference dose can be considered more appropriate, because these molecules show an acute toxicity. Dietary exposure assessment is linked both to the levels of marine biotoxins present in bivalve molluscs and the portion that could be eaten by consumers. Symptoms may vary from a severe gastrointestinal intoxication with diarrhoea, nausea, vomiting and abdominal cramps to neurological disorders such as ataxia, dizziness, partial paralysis and respiratory distress. The official method for the detection of marine biotoxins is the mouse bioassay (MBA) showing some limits due to ethical restrictions and insufficient specificity. For this reason, the liquid chromatography-mass spectrometry method has replaced MBA as the reference technique. However, the monitoring of algal blooms producing marine biotoxins should be regularly assessed in order to obtain more reliable, accurate estimates of bloom toxicity and their potential impacts.